BaliMall.id Integrated Marketing Communication Strategy in Building a Brand Image as an E-Marketplace by Balinese People (E-Jurnal Medium, 2022)
Brand image is a very important factor for new businesses to attract customer or users, one ofwhich is BaliMall.id. The purpose of this research is to see BaliMall.id's integrated marketingcommunication strategy in building a brand image as an E-Marketplace created by Balinesepeople. This study uses a qualitative approach. Data collection techniques using observation,interviews, and documentation. In this study, the key informants were the CEO, the PublicRelations staff, and the user. The data analysis used in this research is qualitative. BaliMall.iduses integrated marketing communications to support success in building a brand image whichare advertising, sales promotion, direct marketing and internet marketing, public relations,personal selling, Event and Experience, and Word of Mouth.Keywords:, E-Marketplace, brand image, integrated marketing communication